Un pas de plus vers le décloisonnement des institutions financières au Canada - Dumont, Monique (Assurances)

(untitled) (HEC Montréal, 1985)
Deregulation of financial institutions is a matter of increasing interest in Canada. Miss Dumont reviews the situation in Quebec where Bill 75 is beginning to take effect.